2023
DOI: 10.14814/phy2.15638
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training modifies xenometabolites in gut and circulation of lean and obese adults

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…We did not investigate the mechanism underlying the training-induced increase in aromatic lactic acids. However, increases in faecal concentrations have previously been reported for PLA [47], ILA and HPLA [48] in subjects with obesity participating in endurance exercise interventions. This points towards a contribution of the gut microbiome, which is well-known to be affected by physical exercise [47, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not investigate the mechanism underlying the training-induced increase in aromatic lactic acids. However, increases in faecal concentrations have previously been reported for PLA [47], ILA and HPLA [48] in subjects with obesity participating in endurance exercise interventions. This points towards a contribution of the gut microbiome, which is well-known to be affected by physical exercise [47, 49, 50].…”
Section: Discussionmentioning
confidence: 99%
“…This points towards a contribution of the gut microbiome, which is well-known to be affected by physical exercise [47, 49, 50]. Interestingly, a recent study found that serum ILA and HPLA were increased in both lean and obese subjects following an exercise intervention, whereas faecal levels were increased in the obese cohort only [48]. This suggests that exercise may have diverging effects depending on the obesity status.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, acute exercise is reported to increase several microbially derived xenometabolites (Grapov et al., 2019 ). Recent findings suggest that 6 weeks of aerobic exercise training modifies xenometabolites in the gut and circulation of lean and obese humans in a physiologically relevant manner (Kasperek et al., 2023 ). Regarding very short‐term exercise, several significant changes in plasma concentrations of metabolites known to be partially or fully derived from microbial metabolism were reported following a 4‐day cross‐country ski march (Karl et al., 2017 ).…”
Section: Gaps In Knowledge and Future Directionsmentioning
confidence: 99%
“…Previous studies have demonstrated that exercise can modulate the composition and diversity of the intestinal microbes, as well as its metabolites and functions 102 . In addition, the intestinal microbes may also affect exercise-induced inflammation, oxidative stress, muscle damage, and immune responses 103 . In a recent study, swimming exercise has been shown to improve depressive-like behavior and boost immunity through its anti-inflammatory effects, as well as by restoring the balance of gut bacteria, such as Escherichia coli and Lactobacilli 104 .…”
Section: Behavioral Adjustmentmentioning
confidence: 99%